Voltage Controlled Intertwined Spiral Arrays for Reconfigurable Metasurfaces - A. Vallecchi; R. J. Langley; A. G. Schuchinsky (International Journal of Antennas and Propagation)
Reconfigurable bistate metasurfaces composed of interwoven spiral arrays with embedded pin diodes are proposed for single and dual polarisation operation. The switching capability is enabled by pin diodes that change the array response between transmission and reflection modes at the specified frequencies. The spiral conductors forming the metasurface also supply the dc bias for controlling pin diodes, thus avoiding the need of additional bias circuitry that can cause parasitic interference and affect the metasurface response. The simulation results show that proposed active metasurfaces exhibit good isolation between transmission and reflection states, while retaining excellent angular and polarisation stability with the large fractional bandwidth (FBW) inherent to the original passive arrays.